A Review of the Tawny Crazy Ant, Nylanderia fulva, an Emergent Ant Invader in the Southern United States: Is Biological Control a Feasible Management Option? - Wang, Zinan (Insects, 2016)
The tawny crazy ant, Nylanderia fulva (Mayr) (Hymenoptera: Formicidae), has invaded states of the U.S. including Texas, Louisiana, Mississippi, Alabama, Florida, and Georgia. Native to South America, N. fulva is considered a pest in the U.S. capable of annoying homeowners and farmers, as well as displacing native ant species. As it continues to expand its range, there is a growing need to develop novel management techniques to control the pest and prevent further spread. Current management efforts rely heavily on chemical control, but these methods have not been successful. A review of the biology, taxonomy, ecology, and distribution of N. fulva, including discussion of ecological and economic consequences of this invasive species, is presented. Options for future management are suggested focusing on biological control, including parasitoid flies in the genus Pseudacteon, the microsporidian parasite Myrmecomorba nylanderiae, and a novel polynucleotide virus as potential biological control agents. We suggest further investigation of natural enemies present in the adventive range, as well as foreign exploration undertaken in the native range including Paraguay, Brazil, and Argentina. We conclude that N. fulva may be a suitable candidate for biological control.